Alantolactone Enhances the Phagocytic Properties of Human Macrophages and Modulates Their Proinflammatory Functions - Gierlikowska, Barbara; Gierlikowski, Wojciech; Demkow, Urszula (Frontiers in Pharmacology, 2020)
Aim of the study: Phagocytosis is a crucial element of innate immune defense involved in bacteria killing. The aim of our study was to evaluate influence of alantolactone on phagocytosis and cytokines release by macrophages. We assessed whether alantolactone, known as antimicrobial compound, will be able to stimulate immune response of macrophages by increase of S. aureus uptake, phagosome acidification and further stimulation of phago-lysosomes formation. Simultaneously, we tested influence of alantolactone on NF-κB activity and release of cytokines/chemokines. The activity of alantolactone was compared with clarithromycin tested at 20 µM. Methods: The cytotoxicity of alantolactone as well as S. aureus uptake, pH of phagosomes and phago-lysosomes fusion were analysed with flow cytometry. Reactive oxygen spices and superoxide production was evaluated spectrophotometrically. The efficiency of phagocytosis was evaluated via quantifying viable bacteria (CFU). The effect on NF-κB and cytokine production by macrophages was measured by enzyme-linked immunosorbent assay (ELISA). Results: Alantolactone tested at wide concentration range (1-20 µM) did not show cytotoxic effect. Alantolactone enhances phagocytosis, one of main components of innate immune response via increase of S. aureus uptake, acidification of phagosomes and later stimulation of phago-lysosomes fusion. Additionally, alantolactone decreased ROS and superoxide production at all tested concentrations. Alantolactone decreased of pro-inflammatory cytokines TNF-α, IL-1β, IL-6 and IL8 production, probably by attenuating the NF-κB transcription factor. Simultaneously, alantolactone stimulated production of anti-inflammatory mediators e.g. IL-10 and TGF-β. Conclusion: Results of our study indicate that alantolactone may enhance clearance of S. aureus, and simultaneously modulates immune response, what may prevent collateral damage. Considering the importance of phagocytosis in the pathogen killing, alantolactone may have a great potential for the supportive treatment of S. aureus infections in the future.